Study of Mechanical and Physical Properties of Epoxy Resins Supported by Natural Materials (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this research the composites materials were prepared by (hand layout). The composites material consist of the base material (epoxy resin) and consist from the support material is the powder of olive seeds with micro size of this material is (53µm) with different weight ratios (0, 0.75, 1.5, 2.25, 3 %) respectively. Also (tensile and impact) and thermal conductivity were studied. The results showed that the best was to test the impact at the weight ratio (1.5 %). As for the thermal conductivity test was the best result in the weight ratio (3%)